Reporte de caso: Cambios cinemáticos post retiro de sarcoma del miembro anterior en un canino - Ortiz-Álvarez, José Fernando (2022)
Gait kinematic analysis is used to quantify the biomechanical parameters integrated in the movement of a body. The case of a female canine patient with a large soft tissue sarcoma located in the elbow region and involving muscular structures is presented. The conventional treatment of this type of tumour includes amputation of the limb, but after evaluating the case supported by magnetic resonance imaging (MRI), it was decided to remove the mass including part of the biceps and triceps muscles. Given the lack of information on this type of treatment in preserving limb functionality, a kinematic analysis of the gait before and after the procedure was performed to quantify the real changes generated.